Health Belief Model Application Related to Safe Work Behavior Against Poisoning Prevention in Farmers Using Pesticides - suharmanto, suharmanto; Hadibrata, Exsa; Wintoko, Risal (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
The World Health Organization estimates that pesticide poisoning occurs yearly in the world and Indonesia. This study aimed to analyze the influence of the Health Belief Model related to safe work behavior on the prevention of poisoning in farmers who use pesticides. This type of research is observational analytic, with a sample of 400 people. The data collection tool used a questionnaire. Data processing includes coding, tabulating, and cleaning. Data analysis used univariate (percentage) and bivariate using the Chi-Square test. The study found a relationship between the dimensions of the Health Belief Model related to safe work behavior on preventing poisoning in farmers who use pesticides. The conclusion of this study is that there is a relationship between the dimensions of the Health Belief Model and the prevention of poisoning in farmers who use pesticides, so it is hoped that the community can increase their knowledge by reading books, attending seminars, counseling and training related to the prevention of poisoning due to the use of pesticides. ABSTRAK World Health Organization memperkirakan setiap tahun terjadi keracunan pestisida di dunia dan Indonesia. Tujuan penelitian ini adalah menganalisis pengaruh Health Belief Model terkait perilaku kerja aman terhadap pencegahan keracunan pada petani pengguna pestisida. Jenis penelitian ini observasional analitik, dengan sampel 400 orang. Alat pengumpul data menggunakan kuesioner. Pengolahan data meliputi coding, tabulating dan cleaning. Analisis data menggunakan univariat (persentase) dan bivariat menggunakan uji Chi-Square. Penelitian mendapatkan adanya hubungan dimensi Health Belief Model terkait perilaku kerja aman terhadap pencegahan keracunan pada petani pengguna pestisida. Simpulan penelitian ini adalah ada hubungan antara dimensi Health Belief Model dengan pencegahan keracunan pada petani pengguna pestisida, sehingga diharapkan kepada masyarakat agar dapat meningkatkan pengetahuannya dengan cara membaca buku, mengikuti seminar, penyuluhan dan pelatihan terkait pencegahan keracunan akibat penggunaan pestisida.